Penerapan Joyful Learning Dalam Upaya Peningkatan Minat dan Hasil Belajar Matematika - Ramadhani, Annisa; Nurhadi; Aprilia, Rustina; Azainil (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
This research discusses the application of Joyful Learning which aims to determine students' interest and learning outcomes in mathematics on flat building material in class VII-5. The method used in this research is quantitative. The research instruments used are questionnaires in the form of observation sheets and Learner Worksheets. The data collection technique in this study consisted of conducting a test before the application of Joyful Learning (pre-test) and a test after Joyful Learning (posttest) in one class which became the research subject. Data analysis techniques used, namely validity and reliability tests, normality tests, Wilcoxon tests. The results of this research indicate that the application of the Joyful Learning model is proven to be able to increase student interest and learning outcomes. This is because the learning is fun and makes students play an active role in the learning process. Thus it can be concluded that the Joyful Learning model has a positive effect on student interest and student math learning outcomes on flat building material. Keywords: Joyful Learning, Learning Outcomes, Interest in Learning